Teachers' professional development through teachers' professional activities. Issue 8 (16th October 2018) - Sharma, Payal; Pandher, Jagwinder Singh
Abstract : Purpose: This study aims to identify various teachers' professional activities (TPAs) and classify these TPAs according to their relative importance for the professional development of teachers. Design/methodology/approach: The systematic review of the literature had been conducted to identify various TPAs in the institutions. Later, an empirical research had been conducted through confirmatory factor analysis using AMOS 20.0 to classify these TPAs according to their relative importance using the natural gap in standardized beta ( β ) values. In total, 96 administrators of 35 technical institutions of Punjab (India) offering engineering and management programs and 93 veteran educational experts had responded in a field survey. Findings: The results of the study identified eight TPAs and further revealed that "regular self-assessment, " "adopting a creative problem-solving approach" and "developing deep commitment to make the difference" qualify among the "most important" activities for the professional enhancement of the faculty. Originality/value: The study highlights different TPAs that they must establish, raise, promote, encourage and organize for their development. The study further classifies different activities according to their relative importance. The institute can evaluate their resources, budgets and efforts according to the relative importance of such activities. The classification of TPAs would help faculty to increase their efficacy.